A revision of the genus Lophomilia Warren, 1913 with description of four new species from East Asia (Lepidoptera: Noctuidae: Hypeninae) - Kononenko, Vladimir; Behounek, Gottfried (Zootaxa, 2009)
The East Asian noctuid genus Lophomilia Warren, 1913 (=Atuntsea Berio, 1977, Bryograpta Sugi, 1977) is revised. Four new species (L. nekrasovi sp. n., L. rustica sp. n., L. diehli sp. n., and L. kobesi sp. n.) are described from Russian Far East, Korea, China and Indonesia, Sumatra. Lophomilia takao Sugi, 1962 and Lophomilia albicosta Yoshimoto 1995 are reported for the first time from China; Lophomilia polybapta (Butler, 1879) is first reported from Russia. The male and female genitalia of most species are described, adults of 12 species from East Asia are illustrated, and distribution maps for all species are presented.